Highly-ordered TiO 2 nanotubes decorated with Ag 2 O nanoparticles for improved biofunctionality of Ti6Al4V - Sarraf, Masoud; Dabbagh, Ali; Bushroa, Abdul Razak; Mahmoodian, Reza; Nasiri-Tabrizi, Bahman; Hosseini, Hamid Reza Madaah; Saber-Samandari, Saeed; Abu Kasim, Noor Hayaty; Abdullah, Hadijah; Sukiman, Nazatul Liana (Elsevier, 2018)
The nanotubular arrays of titanium dioxide (TiO2 NTs) have recently received considerable interest for fabrication of dental and orthopedic implants. However, their antibacterial activity requires substantial improvement for the potential infections minimization, without compromise of their biocompatibility. In this work, TiO2 NTs were developed on Ti6Al4V substrates via anodization at a constant potential of 60 V for 60 min, followed by heat treatment at 500 °C for 90 min. Physical vapor deposition (PVD) was further employed to decorate silver oxide nanoparticles (Ag2O NPs) on the nanotubular edges. The results indicated that the highly-ordered TiO2 NTs with decorated Ag2O NPs could promote the apatite formation and kill 100% of the Escherichia coli (E. coli) bacteria within 2 h. Moreover, proliferation of the human osteoblast cells (HOb) was continuously stimulated throughout culture on the Ag2O NPs-decorated TiO2 NTs. The variation in the viability of HOb cells was statistically insignificant at differed cultivation intervals, indicating the negligible effect of the decorated Ag2O NPs on the osseointegration of these implant materials.